Evaluation of the Salivary Flow Rate and pH in Patients with Recurrent Oral Ulcers - Al-Ahmad, Mustafa; Ezzat, Basma; S, Sukmasari; O, Abdul Jabbar (IIUM Medical Journal Malaysia, 2020)
Introductions: Recurrent oral ulcers primarily effect mucosal surfaces and are among the most common chronic inflammatory diseases. Numerous studies to find the aetiopathogenesis have been conducted however the cause still remains unclear. Saliva is of utmostimportance for oral health maintenance. In current study, saliva was used as a diagnostic tool for comparison of salivary flow rate and pH in patients suffering from recurrent oral ulcers and control group. Materials and Methods: Saliva samples taken from 20 recurrent aphthous ulcer patients and 20 control (healthy) patients using a convient sampling method. Drooling method was used to collect unstimulated whole saliva sample. Pre-weighted specimen bottles were used and then weighed after sample collection on a graduated scale where as chair-side pH meter was used to determine the salivary pH. Independent t-test and Pearson’s correlation were performed. A p-value of less than 0.05 was considered statistically significance. Results: Positive correlation was found between the flow rate and pH in recurrent oral ulcer patients. Patients with recurrent oral ulcers had higher flow rate and pH compared to the control group. These effects were exaggerated in female patients with ulcers. Conclusions: Disturbances in salivary flow rate and pH were not significantly associated with recurrent oral ulcers.